Proximate Composition, Colour, Texture Profile of Malaysian Chicken Balls - Huda, Nurul; Shen, Yap Hui; Huey, Yong Lin (Pakistan Journal of Nutrition, 2009)
The results of the analyses of six brands of commercial chicken balls showed significant differences (p